Densification and Characterization of Rapid Carbothermal Synthesized Boron Carbide - Toksoy, Muhammet Fatih; Toksoy, Muhammet Fatih; Rafaniello, William; Xie, Kelvin Yu; Ma, Luoning; Hemker, Kevin Jude; Haber, Richard Alan (John Wiley and Sons Inc., 2017)
Submicrometer boron carbide powders were synthesized using rapid carbothermal reduction (RCR) method. Synthesized boron carbide powders had smaller particle size, lower free carbon, and high density of twins compared to commercial samples. Powders were sintered using spark plasma sintering at different temperatures and dwell times to compare sintering behavior. Synthesized boron carbide powders reached >99% TD at lower temperature and shorter dwell times compared to commercial powders. Improved microhardness observed in the densified RCR samples was likely caused by the combination of higher purity, better stoichiometry control, finer grain size, and a higher density of twin boundaries.
Keywords: Boron carbide; Spark plasma sintering; Synthesis (Chemistry); Twinning